The significance of roots as hydraulic rheostats - Maurel, Christophe (2010)
Roots are the primary sites of water uptake by plants. Roots also sense most of the physico-chemical parameters of the soil, perceive signals from the shoots, and adjust their growth and water transport properties accordingly. The present opinion paper discusses the significance of the variable water transport capacity (hydraulic conductance) of roots during development and in response to environmental stimuli. It is shown that root hydraulics determines water uptake intensities but also water potential gradients within the plant. It is indicated how the dynamics of root hydraulics contributes to many integrated plant nutritional and growth functions. For instance, the heterogeneity of soil water and nutrient availability and the heterogeneity of root hydraulic properties feed each other and play critical roles in root transport functions. Another important aspect is the integration of root hydraulics within the mutual interactions of roots and shoots, for co-ordinated growth and water-saving responses to drought.